Factors influencing electrics and electronics export performance in Malaysia / Noor Adyanty Nor Asrad - Nor Asrad, Noor Adyanty (Faculty of Business and Management, 2007)
This paper is aims to identify the factors that influence the electric and electronics export performance in Malaysia from January 2004 until November 2006. This is descriptive research and secondary data is being used in order to finish up this study. The data are gathered from Ministry of International Trade Industry. The research objective of this study are firstly to identify the electric and electronic export performance in Malaysia from January 2004 until November 2006, second to identify the factors influence the electric and electronics export performance in Malaysia from January 2004 until November 2006 and lastly to describe the most affected factor to the electric and electronic export performance in Malaysia from January 2004 until November 2006. .In this study the analysis and interpretation being done by using Microsoft Excel and SPSS. In order to identify the significant of the factors the cross tabulation are used. The finding and analysis identify that the factors influence the export performance are demand of other country towards this electric and electronic product, exchange rate of MYR =USD and change of technology. From all this factors, identify that the demand of the electrics and electronics factors have the most significance towards the export performance. These shows that the following factor is really contribute to the performances of export electric and electronic in Malaysia.